A descriptive study of chiropractors' opinions and practices regarding office-based health product sales - Page Stacey A; Grod Jaroslaw P; McMorland D Gordon (Chiropractic & Manual Therapies, 2012)
Abstract Background Although the sale of non-prescription health products is ubiquitous, the views of health professionals, such as chiropractors, regarding the sale of such products are not well known. Practitioner opinion is important to understand and inform professional practice. The purpose of this study was to describe chiropractors' perspectives and practices on the sale of health care products from practitioners' offices. Methods Chiropractors were invited to provide written comments about health product sales at the end of a fixed choice, mailed survey. Respondents' comments were analyzed using qualitative description. Ethics approval was received from the Conjoint Health Research Ethics Board at the University of Calgary. Results One hundred seven of the 265 respondents (response rate of 51%) provided written comments. Approximately 30 pages of double-spaced, typed text were gathered. Respondents did not consistently endorse or condemn health product sales, and engaged in the practice to greater and lesser extents. While some were opposed to health products sales, some accepted the practice with a degree of ambivalence whereas others clearly embraced it. Some respondents acknowledged a professional conflict of interest in such sales and marketing, and described strategies used to mitigate it. Others provided a range of justifications for the practice. Personal integrity and professional standards were discussed and a need for monitoring identified. Conclusions A wide range of opinions and practices were described and this is consistent with resulting variation in practice. In light of this, standards that facilitate consistency in practice may benefit professionals and the public alike.